Trajetória pessoal e científica de Irène Joliot-Curie pautada em aspectos sociais, políticos e de gênero - Lima, Larissa Cabral [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The female presence in Science History has been increasingly recognized, however, this is an area that still has aspects and theoretical approaches to be explored. A historical and critical study of a scientist's career is capable of exposing social issues, such as gender inequalities. In this work, Irène Joliot-Curie, the chemistry Nobel laureate and member of one of the most famous families in history, was chosen to have her personal and professional trajectory explored. The choice is justified by her scientific relevance and her status as the daughter and wife of famous scientists. Irène's findings on artificial radioactivity, her involvement in feminist movements, her communist positions, but above all, her social and professional performance as a woman, allow pertinent discussions about gender and social issues. Initially, a literature search was conducted to collect the necessary data, in primary, secondary and tertiary sources, and thus your history was identified and organized in chronological order. This enabled the recognition of historical, social, and political aspects that influenced her life and career, in order to explore the dialectics of the internalist and externalist character of the history of science. In order to enable such discussions, an approximation with Historical-Dialectical Materialism was promoted by adopting the ideas of Marxist authors. This initial analytical exercise has highlighted political, social, and gender aspects of this scientist's history and addressed to the insertion of the History of Science in the teaching of Chemistry, contributing to a critical education.

A presença feminina na História da Ciência tem sido cada vez mais reconhecida, entretanto, esta é uma área que ainda tem aspectos e abordagens teóricas a serem explorados. Um estudo histórico e crítico da carreira de uma cientista é capaz de escancarar questões sociais, como as desigualdades de gênero. Neste trabalho, Irène Joliot-Curie, uma nobelista de Química e membro de uma das famílias mais famosas da história, foi escolhida para ter sua trajetória pessoal e profissional explorada. A escolha se justifica pela sua relevância científica e condição de filha e esposa de cientistas famosos. Sua descoberta sobre a radioatividade artificial, seu envolvimento em movimentos feministas, seus posicionamentos comunistas e sua atuação social e profissional como mulher, permitiram discussões pertinentes sobre questões de gênero e sociais. Para isso, um levantamento bibliográfico inicialmente foi feito para a coleta dos dados necessários, em fontes primárias, secundárias e terciárias, e assim sua história foi identificada e organizada em ordem cronológica. Isso possibilitou o posterior reconhecimento de aspectos históricos, sociais e políticos que influenciaram na sua vida e carreira, de modo a explorar a dialética do caráter internalista e externalista da história da ciência. Para que tais discussões fossem possíveis, uma aproximação com o Materialismo Histórico-Dialético foi promovida por meio da adoção de ideias de autores marxistas. Esse exercício analítico inicial destacou aspectos políticos, sociais e de gênero que merecem destaque na história dessa cientista, e poderão ser direcionados para a inserção da história da ciência no ensino de química, colaborando para um ensino crítico.
Irène Joliot-Curie's personal and scientific trajectory based on social, political and gender aspects
Keywords: História da química; Mulheres na ciência; Irène Joliot-Curie; Radioatividade artificial